2018
DOI: 10.3389/fendo.2018.00087
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metabolomic Biomarkers for Endometrial Cancer and Its Recurrence after Surgery in Postmenopausal Women

Abstract: Endometrial cancer (EC) is the most frequent gynecological cancer in developed countries. Most EC occurs after menopause and is diagnosed as endometrioid (type I) carcinomas, which exhibit a favorable prognosis. In contrast, non-endometrioid (type II) carcinomas such as serous tumors have a poor prognosis. Our goal was to identify novel blood-based markers associated with EC subtypes and recurrence after surgery in postmenopausal women. Using mass spectrometry-based untargeted metabolomics, we examined preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 66 publications
(30 reference statements)
2
66
0
Order By: Relevance
“…A population-based case-control study also identified potential biomarkers in relation to EC which were independent of risk factors like obesity and previously known blood samples, and the authors suggest that metabolic profiling may be important in its early detection and risk assessment [28]. Moreover, metabolomics have demonstrated certain metabolites to be associated with histological subtypes [29,30], with recurrence following surgery [29], and with tumor blood flow in EC patients [31]. A recent study has also evaluated plasma sphingomyelins and phosphatidylcholines as biomarkers in EC [32], proposing ratios between specific metabolites as diagnostic and prognostic models.…”
Section: Discussionmentioning
confidence: 95%
“…A population-based case-control study also identified potential biomarkers in relation to EC which were independent of risk factors like obesity and previously known blood samples, and the authors suggest that metabolic profiling may be important in its early detection and risk assessment [28]. Moreover, metabolomics have demonstrated certain metabolites to be associated with histological subtypes [29,30], with recurrence following surgery [29], and with tumor blood flow in EC patients [31]. A recent study has also evaluated plasma sphingomyelins and phosphatidylcholines as biomarkers in EC [32], proposing ratios between specific metabolites as diagnostic and prognostic models.…”
Section: Discussionmentioning
confidence: 95%
“…These glycerides are ultimately metabolised (by the action of monoacylglycerol lipase) to free fatty acids, the group of lipid metabolites that are known to be downregulated in EC. The downregulation of the lipase enzyme in EC may, in theory, account for the observed findings [71,83]. Using plasma samples from women with EC (n = 342), atypical hyperplasia (n = 68) and healthy controls (n = 242) in a cross-sectional diagnostic accuracy study, our group was able to show that spectroscopy has the potential to detect EC with 87% sensitivity and 78% specificity [84].…”
Section: Blood-based Diagnostic Metabolomic Ec Biomarkersmentioning
confidence: 89%
“…Audet-Delage and colleagues, using mass spectrometry-based untargeted metabolomics on pre-operative serum samples of 36 EC cases and 18 controls, reported an upregulation of conjugated lipids including acylcholines, monoacylglycerols and acylcarnitines in EC cases and downregulation of free fatty acids, suggesting the potential remodelling of lipid metabolic pathways in EC [71]. Further, they found C5 acylcarnitine 2-methyl butyryl carnitine was elevated in EC cases [71]. These findings align with those of Bahado-Singh, who also reported an upregulation of acylcholines in EC [77].…”
Section: Blood-based Diagnostic Metabolomic Ec Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations